1990
DOI: 10.1103/physrevd.41.514
|View full text |Cite
|
Sign up to set email alerts
|

Operator regularization and multiloop Green's functions

Abstract: We present in this paper the evaluation of multiloop Green's functions in the context of a recently proposed regulating scheme called operator regularization. We show that, in contrast with other schemes, imposing the requirement of unitarity (rather than finiteness) is crucial in obtaining the (perturbative) renormalized effective action and Green's functions of a given theory. We demonstrate how an evaluation of these quantities may be carried out using this regulating technique in a manner which preserves t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…We use 1) operator regularization (OR) [10,11] and 2) the cutoff regularization method. The first method was proposed a few years ago and regularizes the operators present in the theory instead of modifying the original Lagrangian by either adding counterterms or massive fields.…”
Section: Introductionmentioning
confidence: 99%
“…We use 1) operator regularization (OR) [10,11] and 2) the cutoff regularization method. The first method was proposed a few years ago and regularizes the operators present in the theory instead of modifying the original Lagrangian by either adding counterterms or massive fields.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we have shown that proper-time regularization yields a result in agreement with analytic [6], dimensional [7], operator [8], and nonlocal [9] regularizations, and in disagreement with Pauli-Villars [4] regularization. Nevertheless, we may also reproduce in this context the result of the Pauli-Villars regularization by introducing a Pauli-Villars cutoff in (3.6) as…”
Section: Discussionmentioning
confidence: 54%
“…In the limit m -m , rIF) vanishes as This is to be contrasted with the result obtained via analytic [6], dimensional [7], operator [8], and nonlocal [9] regularizations, which yield a CS term surviving in this limit:…”
Section: Regularization Ambiguity In the Qed Effective Actionmentioning
confidence: 54%
See 2 more Smart Citations